Effects of bentonite on pore structure and permeability of cement mortar. (10th November 2019) - Yang, Hu; Long, Diao; Zhenyu, Lai; Yuanjin, He; Tao, Yan; Xin, He; Jie, Wu; Zhongyuan, Lu; Shuzhen, Lv
Highlights: The effects of bentonite on the pore structure of cement mortar were given. The permeability of mortar could be reduced significantly by bentonite. The waterproofing process and mechanism of bentonite particles were proposed. Abstract: The pore structure and permeability of cement-based materials have great influence on the durability of application of this materials. The effects of bentonite on the pore structure and permeability of cement mortar were investigated in this paper. Bentonite, as a swelling potential clay, was added to mortar at content 0, 4 and 8% by weight of cement. The compressive strength, flexural strength, and impermeability pressure were determined for cement mortar with bentonite and compared with plain cement mortar specimens. Test results showed that the addition of 8% bentonite could cause a significant increase of 61.48%, 42.09% and 76.47% for compressive strength, flexural strength, and impermeability pressure, respectively. The enhancement of impermeability is mainly due to the pore structure refinement by the bentonite, which is validated by test results of the Mercury intrusion porosimetry (MIP). Moreover, needle-like and amorphous hydration products grow on the surface or edge of bentonite resulting in more tortuous penetration path to improve the barrier performance of cement mortar.